2021
DOI: 10.1101/2021.04.17.440006
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Co-evolutionary analysis suggests a role for TLR9 in papillomavirus restriction

Abstract: Upon infection, DNA viruses can be sensed by pattern recognition receptors (PRRs) leading to the activation of type I and III interferons, aimed at blocking infection. Therefore, viruses must inhibit these signaling pathways, avoid being detected, or both. Papillomavirus virions are trafficked from early endosomes to the Golgi apparatus and wait for the onset of mitosis to complete nuclear entry. This unique subcellular trafficking strategy avoids detection by cytoplasmic PRRs, a property that may contribute t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 159 publications
(148 reference statements)
0
4
0
Order By: Relevance
“…Since the authors detected evidence of co-evolution between TLR9 and the viral nucleotide ratio, these changes are likely due to evolutionary pressure provided by evading recognition by the TLR9 protein. Similar to what was seen as a response to APOBEC3 editing, the depletion of CpG does not appear to drastically alter the amino acid content of the viral proteins [ 68 ]. These data support the idea that papillomavirus protein sequences are evolutionarily constrained but that nucleotide sequences are evolving to escape antiviral responses shaping host-virus interactions.…”
Section: Host-pathogen Interactions Shape the Dna Sequence Of Papillo...mentioning
confidence: 81%
See 3 more Smart Citations
“…Since the authors detected evidence of co-evolution between TLR9 and the viral nucleotide ratio, these changes are likely due to evolutionary pressure provided by evading recognition by the TLR9 protein. Similar to what was seen as a response to APOBEC3 editing, the depletion of CpG does not appear to drastically alter the amino acid content of the viral proteins [ 68 ]. These data support the idea that papillomavirus protein sequences are evolutionarily constrained but that nucleotide sequences are evolving to escape antiviral responses shaping host-virus interactions.…”
Section: Host-pathogen Interactions Shape the Dna Sequence Of Papillo...mentioning
confidence: 81%
“…These data suggest that evolution may select nucleotide sequences and not only amino acid residues. By analyzing dinucleotide patterns, we and others identified that specific dinucleotide pairs are less common than what would be expected by chance [ [67] , [68] , [69] , [70] ]. Specifically, there is a dramatic reduction in CpG and TpC dinucleotides ( Fig.…”
Section: Host-pathogen Interactions Shape the Dna Sequence Of Papillo...mentioning
confidence: 99%
See 2 more Smart Citations